2011
DOI: 10.1016/j.virol.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus is not restricted by tetherin whereas influenza VLP production is restricted by tetherin

Abstract: Tetherin (ST2/CD317) is a cellular protein that restricts the release from cells of some enveloped viruses including HIV-1. To examine if influenza virus is affected by tetherin, MDCK cells constitutively expressing human tetherin and control MDCK cells were infected with influenza virus. No difference was observed in infectious titers, at 24 h or 48 h post-infection. In contrast, tetherin expression inhibited influenza virus-like particle (VLP) release into the media. Expression of the HIV protein Vpu overcam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 40 publications
8
57
2
Order By: Relevance
“…Similarly, IFN-inducible transmembrane 3 (IFITM-3) limits replication of IAV and other enveloped viruses in epithelial cells (reviewed in reference 37) by preventing cytosolic entry (38), and IAV replication in M⌽ is blocked later in the virus life cycle. In epithelial cells, tetherin (also named BST-2) and viperin have been implicated in limiting release of nascent virions from the plasma membrane (39)(40)(41); however, our data indicate that nonproductive replication in M⌽ is restricted prior to the development of virus buds. Thus, while studies have implicated particular ISGs in limiting IAV infection of epithelial cells, the factors that block productive IAV replication in M⌽ are not known.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, IFN-inducible transmembrane 3 (IFITM-3) limits replication of IAV and other enveloped viruses in epithelial cells (reviewed in reference 37) by preventing cytosolic entry (38), and IAV replication in M⌽ is blocked later in the virus life cycle. In epithelial cells, tetherin (also named BST-2) and viperin have been implicated in limiting release of nascent virions from the plasma membrane (39)(40)(41); however, our data indicate that nonproductive replication in M⌽ is restricted prior to the development of virus buds. Thus, while studies have implicated particular ISGs in limiting IAV infection of epithelial cells, the factors that block productive IAV replication in M⌽ are not known.…”
Section: Discussionmentioning
confidence: 62%
“…Given that leukocytes, including CD4 ϩ T cells, exist in dense clumps and are in contact with each other in lymphoid tissues (e.g., spleen), it is feasible to assume that HIV-1 dissemination is more likely to occur through cell-to-cell contact in vivo. Moreover, previous reports have demonstrated that BST2 potently impairs the release of Orthomyxoviridae (influenza A virus) and Filoviridae (Ebola virus and Marburg virus); however, BST2 does not suppress the spread of these viruses in in vitro cell cultures (47,69). Therefore, it is conceivable that BST2 does not impair the cell-to-cell spread of viruses even if the cell-free virus-mediated infection of these viruses is restricted by BST2.…”
Section: Discussionmentioning
confidence: 99%
“…The restriction conferred by BST2 is not limited to retroviruses (9,23,26) but also various enveloped viruses belonging to Filoviridae (Ebola virus and Marburg virus) (23,24,49), Arenaviridae (Lassafever virus) (49), Herpesviridae (Kaposi's sarcoma-associated herpesvirus) (34), Rhabdoviridae (vesicular stomatitis virus) (71), Orthomyxoviridae (influenza A virus) (69), and Paramyxoviridae (Nipah virus) (47). However, some of these viruses possess their own antagonizing BST2 counterparts instead of Vpu.…”
Section: Wt]) Hiv-1-infected/transfected Cells In Certain Cd4mentioning
confidence: 99%
“…The species-specific resistance to tetherin was unexpected given that tetherin functions broadly in a structure-dependent manner (40). However, there is precedent for our observation, as human tetherin, but not canine tetherin, could restrict budding of influenza A virus VLPs from MDCK cells (44). The molecular basis for the functional difference between human and mouse tetherin remains to be fully defined, but our mapping studies suggest a role for the tetherin cytoplasmic tail (Fig.…”
Section: Hiv-1 Vpumentioning
confidence: 71%